Robust flight control design for a turn coordination system with parameter uncertainties - Legowo, Ari (IIUM Press, 2009)
This paper presents a method of robust control system design foe aircraft flight control systems with the existence of uncertainty parameters such as stability and control derivatives resulted by parameter identification process using real test data. A nonlinear model of aircraft turn coordination system is considered. The problem is to find the optimal controller by using H..optimal control method combined with a quasi-Newton optimization method. The present method designs the gain of the cross pass channel for the aileron and rudder interconnect, which causes nonlinearity of the system. The robust controller design is qualified in designing the H.. optimal control under a given value of the 'nonlinear' gain, and sequentially determining the optimal 'nonlinear' gain subject to minimize the error performance of the turn coordination system by using the quasi-Newton method. The perturbations of the uncertainties model have structured uncertainties constructed by the differences between the aerodynamic coefficients derived by parameter identification process and wind tunnel result. The proposed method is applied to the real flight test data of N250 PA-1 aircraft.